Social psychology of the workplace - Thye, Shane R.; Lawler, Edward J. (Emerald, 2006)
Advances in Group Processes publishes theoretical analyses, reviews and theory based empirical chapters on group phenomena. Volume 23 includes papers that address fundamental issues relating to the Social Psychology of the Workplace. Chapter one uses a social identity perspective to understand the emergence of social capital and cooperative behavior in the workplace. The second and third chapters address issues of leadership. Chapter two reviews the social psychological literature on leadership, and contrasts this with leadership literatures which tend to be more applied (and positive) in nature. The third chapter offers a new theory of leadership that centers on the importance of leadership vision and self-sacrifice. As a group, these chapters address new empirical and theoretical problems at the cutting edge of workplace research. The next two chapters take on issues gender and inequality.-Chapter four compares and contrasts two classes of theoretical explanations for gender inequality: economic theories of statistical discrimination and social psychological theories of status discrimination. After evaluating both programs of research, the paper illustrates how status based theories may be relaxed to encompass more of the empirical landscape. The next chapter examines how legitimacy (or a lack thereof) in male or female dominated organizations can produce salient gender stereotypes. The authors report data from a new laboratory experiment, and find support for a number of the basic relationships that are predicted. Readers interested in issues pertaining to gender in the workplace should find both chapters appealing. Issues of power and status are at the core of the next chapters. Chapter six asserts that the concept of hierarchy has been neglected in a number of research areas in the organizational domain.-The paper shows how greater attention to status and power hierarchies can increase our understanding of group decision making, conflict management, and performance. Chapter seven illustrates how principles from network exchange theory and expectation states theory are broadly applicable to issues of leadership in organizations and academia. Together, these two chapters make a strong case that theories of power and status have much to offer in explaining the social psychology of the workplace. Two chapters address issues of legitimacy. Chapter eight explores how procedural justice and collective legitimacy jointly produce negative emotions in the workplace. This chapter develops a number of hypotheses regarding how it is that collective legitimacy impacts perceptions of procedural justice when people do not receive the rewards that they expect.-Chapter nine theoretically distills the relationship between legitimacy and trust, focusing specifically on ways that these processes interface with research on leadership in organizations. The final two chapters explore some of the broader social psychological issues of the workplace. Chapter ten draws on the larger identity maintenance literature to explain selective identity preference in occupational settings. Specifically, the paper details how individuals choose among potential future identities when all other benefits are essentially the same. The final chapter explores the emergence of propane markets in the southern United States, documenting the theoretical principles of market structure and cataloguing the problems such markets face. Overall, the volume includes papers that reflect a wide range of theoretical approaches to the social psychology of the workplace, and contributions by major scholars from multiple disciplines that work in the general area of group processes.-This book addresses gender and inequality in the workplace, considers leadership theories, and reviews the hierarchy structure of organizations.
Part of the Advances in Group Processes, which publishes theoretical analyses, reviews and theory based empirical chapters on group phenomena. This volume includes papers that address fundamental issues relating to the Social Psychology of the Workplace.
Keywords: Social psychology.; elektronické knihy; electronic books